(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
The study was carried out to scrutinize the perception of Gen Z based on the KOLs’ food review on Tiktok platform in Vietnam and FPT University students’ perspective as an addition to this research. Most important, the research aims to help social media users become wiser in selecting and identifying useful information. 203 students from a private University in Vietnam provided the data. Content analysis for analyzing contents and 5-point Likert scale for making a survey were used throughout the study’s execution, which took place between August 2022 and November 2022. According to research, TikTok content about food reviews influences Gen Z customers’ purchase intentions in four different ways, all of which are favorable. These variables are information, entertainment, trust, and social connection and they all have favorable and unfavorable effects on the intention to make a decision about trying different dishes. In which the information component has the greatest influence on Gen Z consumers’ intentions to make an online purchase and to try new foods. Based on the findings of the study, suggestions are provided to assist the students in having the right decisions made when it comes to absorbing new information and trying different types of meals in Vietnamese and some other cuisines.